Building New Concepts: Concepts in Indigenous Architecture as Interdisciplinary Enhancement Factor? - Tochtermann, Verena; Justus Liebig University Giessen (My University, 2018)
In contrast to the marginalization of indigenous cultures in architectural analysis, research on indigenous architecture has revealed extraordinary uses of concepts. The difficulty of analyzing the often decategorized buildings not only uncovers the need to improve methods of analysis, but also offers new approaches to analytical methodologies. In particular, the unconventional way of conveying concepts in indigenous architecture offers parameters for rebuilding the limiting boundaries. Following challenges in and research on new methodologies in other disciplines, as represented by Mieke Bal in cultural analysis with the idea of travelling concepts, indigenous architecture promises new perspectives. This contribution therefore presents selected indigenous architectural traditions in Central America, along with their conceptual contents and potential to expand analytic criteria. To stress the diversity of concepts, the first part introduces selected buildings by presenting differences and similarities between architectural principles and intentions. After exposing the limits of typological analysis and the potential of entangled concepts, the article analyzes case studies through terms from Bal s book Travelling Concepts in order to converge the character of indigenous architecture. Finally, the article considers how entangling concepts could generate new perspectives in the architectural discourse as well as in other disciplines.
Keywords: architecture; Central America; cosmovision; indigeneity; travelling concepts; ddc:300